ANALISIS PERUBAHAN SUHU PEMANASAN PADA STAINLESS STEELS 304 - Gumono Gumono; R. N. Akhsanu Takwim; Sugeng Hadi (INFO-TEKNIK, 2017)
Stainless steels are widely used for household purposes, such as spoons, forks and knives that serve as cutting tools are currently widely used. Based on the micron structure this metal is grouped into austenitic, ferritic, martensitic, duplex and prepication hardening. The purpose of writing determines the optimum hardness value of stainless steel 304 after getting treatment with nitrogen media. Gets optimum hardness when using nitric acid media. At what temperature and what type of cooling is used to obtain optimum hardness. Research method by comparing stainless steel before and after experiencing heat treatment process by using nitrogen cooling medium and nitric acid. Hardness testing using rockwell method. Optimum hardness results occur at 400 °C with 20.33HRc nitrogen cooling medium and 500 °C of nitric acidic acid 19,67HRc